The economics of politically connected firms - Jay Pil Choi; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2007)
Political connections between firms and autocratic regimes are not secret and often even publicly displayed in many developing economies. We argue that tying a firm's available rent to a regime's survival acts as a credible commitment forcing entrepreneurs to support the government and to exert effort in its stabilization. In return, politically connected firms get access to profitable markets and are exempted from the regime's extortion. We show that such a gift exchange between government and politically connected firms can only exist if certain institutional conditions are met. In particular, the stability of the regime has to be sufficiently low and the regime needs the power to exploit independent firms. We also show that building up a network of politically connected firms acts as a substitute for investments in autonomous stability (such as spending on military and police force). The indirect strategy of stabilizing a regime via politically connected firms gradually becomes inferior when a regime's exploitative power rises.
Keywords: H1; H26; H32; L1; 330; Patronage; Öffentliches Unternehmen; Public Choice; Politische Stabilität; Rent Seeking; Theorie